Implant Design and the Anchoring Mechanism Influence the Incidence of Heterotopic Ossification in Cervical Total Disc Replacement at 2-year Follow-up. Issue 21 (1st November 2019) - Mehren, Christoph; Wuertz-Kozak, Karin; Sauer, Daniel; Hitzl, Wolfgang; Pehlivanoglu, Tuna; Heider, Franziska
Abstract : Study Design: A nonrandomized, prospective, and single-center clinical trial. Objective: The aim of this study was to determine whether the prosthesis design, and especially changes in the primary anchoring mechanism between the keel-based ProDisc C and the spike-based ProDisc Vivo, affects the frequency of heterotopic ossification (HO) formation over time. Summary of Background Data: The occurrence of motion-restricting HO as well as underlying risk factors has so far been a widely discussed, but not well understand phenomenon. The anchoring mechanism and the opening of the anterior cortex may be possible causes of this unwanted complication. Methods: Forty consecutive patients treated with the ProDisc C and 42 consecutive patients treated with the ProDisc Vivo were compared with respect to radiological and clinical outcome, with 2 years of follow-up. Clinical outcome scores included the Neck Disability Index (NDI), Visual Analogue Scale (VAS), and arm and neck pain self-assessment questionnaires. Radiological outcomes included the segmental lordosis and range of motion (ROM) of the index-segment as well as the occurrence of HO. Results: The clinical outcome parameters improved in both groups significantly. [ProDisc C: VAS arm and neck pain from 6.3 and 6.2 preoperatively to 0.7 and 1.3; NDI from 23.0 to 3.7; ProDisc Vivo: VAS arm and neck pain from 6.3 and 4.9 to 1.4 and 1.6, NDI from 34.1 to 8.7; 2-year follow-up (FU)]. The ProDisc Vivo cohort demonstrated a significantly lower incidence of HO than the ProDisc C group at 1-year FU ( P  = 0.0005) and 2-year FU ( P  = 0.005). Specifically, high-grade HO occurred in 9% versus 31%. Conclusion: These findings demonstrate that prosthesis designs that allow primary anchoring without violation of the cortical surface help to reduce the incidence of severe ossification, possibly affecting the functionality and mobility of the artificial disc device over of time. Level of Evidence: 3 Abstract : Within a nonrandomized, prospective, and single-center clinical trial, 40 or 42 patients received a single-level treatment with the ProDisc C or ProDisc Vivo, respectively. The incidence of heterotopic ossification was significantly lower in the ProDisc Vivo group. Clinical parameters improved significantly over time in both groups.